1991
DOI: 10.1111/j.1471-4159.1991.tb06344.x
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Transduction Mechanism for the Glutamate Action on Phosphoinositide Metabolism via the Quisqualate Metabotropic Receptor in Rat Brain Synaptoneurosomes: II. Calcium Dependency, Cadmium Inhibition

Abstract: In this article, we demonstrate that an increase in intracellular Ca2+ concentration may represent a specific common step(s) in the mechanism(s) of action of glutamate (Glu) and depolarizing agents on formation of inositol phosphates (IPs) in 8-day-old rat forebrain synaptoneurosomes. In fact, A23187, a Ca2+ ionophore, induces a dose-dependent accumulation of IPs, which is not additive with that evoked by Glu and K+ but is slightly synergistic with that induced by carbachol. In addition, Glu and K+ augment the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 59 publications
0
5
1
Order By: Relevance
“…Glial cells expressing mGluRs might be activated by glutamate released by neurons, and then indirectly regulate the frequency of neural Ca 2+ spikes. Some reports have indicated that glutamate acting on mGluRs increases intracellular Ca 2+ concentrations in astrocytes (Guiramand et al, 1991;Jensen and Chiu, 1990) in addition to neurons (Courtney et al, 1990;Llano et al, 1991). However, changes in the frequency of synchronized Ca 2+ spikes according to the activation of the mGluRs in this report were changes of neural Ca 2+ spikes, because they were accompanied by action potentials, and small cell bodies of neurons visualized by fura-2 apparently differed from the flat, practically invisible in the present experiments, morphology of astrocytes (Suzuki et al, 2003).…”
Section: Discussioncontrasting
confidence: 74%
“…Glial cells expressing mGluRs might be activated by glutamate released by neurons, and then indirectly regulate the frequency of neural Ca 2+ spikes. Some reports have indicated that glutamate acting on mGluRs increases intracellular Ca 2+ concentrations in astrocytes (Guiramand et al, 1991;Jensen and Chiu, 1990) in addition to neurons (Courtney et al, 1990;Llano et al, 1991). However, changes in the frequency of synchronized Ca 2+ spikes according to the activation of the mGluRs in this report were changes of neural Ca 2+ spikes, because they were accompanied by action potentials, and small cell bodies of neurons visualized by fura-2 apparently differed from the flat, practically invisible in the present experiments, morphology of astrocytes (Suzuki et al, 2003).…”
Section: Discussioncontrasting
confidence: 74%
“…Specifically, the bathing solution was switched to either zero calcium–EGTA Krebs solution or the Ca 2+ was replaced by Cd 2+ . Predictably (Ciardo & Meldolesi, 1991; Guiramand et al 1991), both of these conditions essentially blocked the effects of glutamate to elevate cytoplasmic Ca 2+ in NST neurones (data not shown).…”
Section: Resultsmentioning
confidence: 82%
“…In addition, we have shown that some divalent cations, such as Cd2+ and Ba2+, stimulate formation of IPS and depolarize the synaptoneurosomal membrane (see Guiramand et al, 1991). The stimulation of formation of Ips by Cd" has also been reported in human skin fibroblasts (Smith et al, 1989).…”
Section: Relationship Between Membrane Depolarization and Metabolism mentioning
confidence: 72%